Donor‐specific individuality of red blood cell performance during storage is partly a function of serum uric acid levels. Issue 1 (23rd October 2017) - Tzounakas, Vassilis L.; Karadimas, Dimitrios G.; Anastasiadi, Alkmini T.; Georgatzakou, Hara T.; Kazepidou, Eleftheria; Moschovas, Dimitris; Velentzas, Athanassios D.; Kriebardis, Anastasios G.; Zafeiropoulos, Nikolaos E.; Avgeropoulos, Apostolos; Lekka, Marilena; Stamoulis, Konstantinos E.; et al.
Abstract : BACKGROUND: Previous investigations in leukoreduced units of red blood cells (RBCs) in mannitol additive solution revealed the close association of uric acid (UA) levels in vivo with the susceptibility of RBCs to storage lesion markers. In this study, we examined whether UA has a similar correlation with the capability of RBCs to cope with the oxidative provocations of storage under different conditions, namely, in CPDA‐1 and in the absence of leukoreduction. STUDY DESIGN AND METHODS: The UA‐dependent antioxidant capacity of the supernatant was measured in nonleukoreduced units of RBCs in CPDA (n = 47). The possible effect of UA variability on the storage lesion profile was assessed by monitoring several physiologic properties of RBCs and supernatant, including cell shape, reactive oxygen species, and size distribution of extracellular vesicles, in units exhibiting the lowest or highest levels of UA activity (n = 16) among donors, throughout the storage period. RESULTS: In stored RBC units, the UA‐dependent antioxidant activity of the supernatant declined as a function of storage duration but always in strong relation to the UA levels in fresh blood. Contrary to units of poor‐UA activity, RBCs with the highest levels of UA activity exhibited better profile of calcium‐ and oxidative stress–driven modifications, including a significant decrease in the percentages of spherocytes and of 100‐ to 300‐nm‐sized vesicles, typically associated with the exovesiculation of stored RBCs. CONCLUSION: The antioxidant activity of UA is associated with donor‐specific differences in the performance of RBCs under storage in nonleukoreduced CPDA units.